Health information seeking behavior of female breast cancer patients - Ghazavi-Khorasgani, Zahra (J Educ Health Promot, 2018)
BACKGROUND AND AIM: One of the methods for involving breast cancer patients in their own treatment is to provide them with credible and simple information. To provide this information, it is first necessary to investigate health information-seeking behaviors of these patients including their information needs, sources, barriers, and attitudes regarding health information. METHODS: This is an applied type study using survey method. The statistical population included female breast cancer patients referring to Seyed-Al-Shohada Hospital of Isfahan (60 patients). Data gathered through questionnaire. RESULTS: “Self-care,” “emotional-psychological support information,” and “treatment length and chance of relapse” were the most sought-after health information by patients. “Brochure and catalog provided by hospital,” “other cancer patients,” and “physicians and nurses” were the most important information sources. “High cost of information sources,” “Lack of response from treatment personal (physicians and nurses),” and “lack or trust in website information” were the most important information-seeking barriers. Regarding attitude, participants stated that health information can help them in areas such as “controlling their conditions,” “adapting to their conditions,” “stress and anxiety control,” and “preforming their social roles” and “hopefulness.” CONCLUSION: Credible and relevant information can help patients to seek their treatment with renewed motivation and energy. This information should be provided for the patients from various sources such as brochures and websites according to their information-seeking abilities and health literacy with low cost. The knowledge of library and medical information experts can be used for evaluation and creation of easy-to-understand information sources.